Impact of centralized and individual heating systems in residential buildings from Environmental Considerations. Case study for Chisinau - Tirsu M.S.; Lupu M.L.; Postoronca Sv.A. (Problems of the Regional Energetics, 2019)
The paper aims to provide argumentation of centralized district heating system use from the consideration of harmlessness for both public health and environment, in comparison with the use of individual heating units, installed in residential areas of the Chisinau municipality. Proposed goal have been reached performing the comparison on quantitative harmful emissions resulting from the operation of these two types of heating, using emissions factors, deducted from the specific consumption of thermal energy. The issue's relevance is proved by the existence of considerable number of disconnected users from the centralized heating, though last years, this trend is decreasing. As regard to new buildings, they continue to give priority to the individual heating. Statistical data provided by specialized institutions of the municipality underlines the increased share of incidents of intoxication with combustion products, namely carbon oxide, followed by poisoning from gas leaks, shingles caused by explosions in violation of the operating rules of such equipment, also registering lethal cases. New results are the determination of the difference in emission values for both cases. The importance of the obtained results is that for the generation of thermal energy in a centralized heating system using cogeneration technology, harmful emissions into the environment are 28% less than when using individual heat supply systems. This received ascertainment could serve as an important argumentation for the obvious priority of the centralized heating system in the municipality versus the use of individual units.